Crystal structure of ceftriaxone sodium hemiheptahydrate, C18H16N8O7S3Na2(H2O)3.5. Issue 3 (September 2020) - Gonzalez, Diana; Golab, Joseph T.; Eilert, Jan Y.; Wang, Rong; Kaduk, James A.
Abstract : The crystal structure of ceftriaxone sodium hemiheptahydrate has been solved and refined using synchrotron X-ray powder diffraction data and optimized using density functional techniques. Ceftriaxone sodium hemiheptahydrate crystallizes in the space group C 2 (#5) with a = 30.56 492(16), b = 4.75 264(2), c = 18.54 978(16) Å, β = 90.3545(6), V = 2694.562(21) Å 3, and Z = 4. Both Na exhibit trigonal bipyramidal coordination. Prominent in the structure are alternating Na/O and organic layers perpendicular to the c -axis. There are many O–H⋯O hydrogen bonds involving the water molecules and the ionized portions of the anion. There are a surprising number of C–H⋯S hydrogen bonds, as well as C–H⋯N and C–H⋯O hydrogen bonds. The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File™.